“Risky Forays into Border Lands”: „Bez autorytetu” by Stefan Chwin and Stanisław Rosiek, and the Depleting Modernity - Kaliszuk, Przemysław (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article concerns a critical book by Stefan Chwin and Stanisław Rosiek, titled Bez autorytetu, which is treated as an example of the process of a certain turn in the Polish modern literature of the end of the 20th century. The author discusses the basic assumptions of critical concepts and indicates the questionable places of the problem structure emerging from those assumptions. In so doing, he treats Bez autorytetu as a form of a modern essay which developed in the conditions of mature modernism, which was reflected in the various attempts at transcending modernistic conditions, both formal and conceptual.